Identification of Tannin, Triterpenoid, and Flavonoid Function Groups of Jamblang Plants (Syzygium cumini): A Systematic Literature Review - Aliffia Dwi Rahma; Hanifah Ismayfatin; Yulianti Khasanah; Aditiya Rizky Putra Abimanyu; Hidayah, Himyatul (HM Publisher, 2024)
Identification of the functional groups of tannins, triterpenoids, and flavonoids in jamblang is important to determine the type and content of bioactive compounds found in jamblang. By knowing the type and content of these bioactive compounds, the potential of jamblang as a traditional medicine can be further optimized. This study aims to explore the identification of tannin, triterpenoid, and flavonoid functional groups in jamblang. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the identification of tannin, triterpenoid, and flavonoid functional groups in jamblang (Syzygium cumini). This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. Jamblang contains various types of tannins, including catechins, gallotanins, and proanthocyanidins. Jamblang contains various types of triterpenoids, including phytosterols, triterpenoid saponins, and other triterpenoids. Jamblang contains various types of flavonoids, including flavonols, flavanones, and anthocyanins.